Endovascular Treatment of Hepatic Venous Outflow Obstruction after Liver Transplant - Pandhi, Mithil B.; Lipnik, Andrew J.; Niemeyer, Matthew M. (Digestive Disease Interventions, 2019)
Liver transplantation provides definitive treatment to address acute or chronic end-stage liver disease and its complications. Hepatic venous outflow obstruction is an infrequent complication of liver transplantation that affects graft survival by compromising outflow via transplant hepatic veins or inferior vena cava. It can occur in the early postoperative phase or in a delayed manner, resulting in venous congestion, graft dysfunction, graft failure, and death. This article addresses the pathophysiology of venous outflow obstruction as it relates to different surgical techniques and patient populations, the noninvasive tools for diagnosis, and the endovascular options for treatment along with their safety, efficacy, and durability.
Keywords: hepatic venous outflow obstruction; liver transplant; stent; stenosis